A Contemporary Reading of Sophocles' Oedipus Rex. Presidential Elections of 2018 in Costa Rica - Hidalgo Xirinachs, Roxana (2024)
The article addresses the potential of Greek Tragedy to be used to approach social issues, specifically the political and religious crisis that Costa Rican society is going through and that reaches a climax during the 2018 presidential elections. The main objective is to have a socio-historical interpretation of Sophocles´ Oedipus Rex in order to show how the play could provide keys to understanding a society in transition that experienced social polarization and political confrontation marked by complex experiences of rupture of the social bond. To address this purpose, we complement the interpretation of the tragedy with a follow up of some Latin American and classical adaptations that follow the trail of the myth. And based on sources of the time and specialized bibliography, we approach the social context of the crisis of legitimacy that Costa Rican democracy faces linked to the rise of religious fundamentalism and the neoliberal worldview of the market.